An Approach to the State of Family Zeal under the Shadow of Iranian Jurisprudence and Law - zahra lame; Fateme Fallah Tafti (فقه و حقوق خانواده)
Zeal means a change in the natural mood of a man and his inner transformation to protect his/ her privacy. This significant characteristic has been praised in our religious texts with phrases such as the necessity of humanity and the characteristic of a pious person, and the conditions and terms have been designated for it in the Islamic jurisprudence. One type of zeal is the zeal of family, which has been contested for its sensitivity, and on the other hand, has been used by the enemies of Islam to sabotage the image of the religion. This article has been written in a descriptive-analytical method and with the aim of correctly explaining of this kind of zeal and its criteria from the viewpoint of Imami jurisprudence. The findings of this article, which are based on a detailed analysis of the examples of family zeal in jurisprudence, delineates that the most vital jurisprudential criteria for family zeal are the committing of an act of violation of chastity by a woman in the time of Idah, the need to meet the conditions of the permission to kill in case the wife is unfaithful, hijab and chastity by women are not observed, and wife decency, family privacy and protection have not been met. Criteria such as running away from home, suspicion and rumors, confidential marriages, refusal of forced marriages, etc., which are seen in the cases related to the discussion of zeal, have no Shariah justification and rational, and therefore this article proposes to amend the legal elements in this matter. It has the expression of conditions as well as culture cultivation in this field.